2007
DOI: 10.1080/14034940600975781
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Child health in Greenland

Abstract: A relatively high child mortality but the same morbidity pattern as in other Western societies was found. Negative health behaviour is frequent in schoolchildren. The influence of rapid cultural changes, and familial and societal factors related to social ill health, together with socioeconomic inequity, are of major importance to the health of children in Greenland. More accurate data on child health are necessary in the future to secure better prioritization. It is suggested to construct a set of reliable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 38 publications
0
30
0
6
Order By: Relevance
“…Vigorous physical activity explicitly encompasses a dimension of physical activity as a recreational pursuit or hobby. A confirmatory factor analysis among adolescent girls indicated that the measures express different behavioural patterns and may even have different outcomes (4).…”
Section: Discussionmentioning
confidence: 99%
“…Vigorous physical activity explicitly encompasses a dimension of physical activity as a recreational pursuit or hobby. A confirmatory factor analysis among adolescent girls indicated that the measures express different behavioural patterns and may even have different outcomes (4).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier on, perinatal complications, acute and chronic infectious diseases and injuries dominated as causes of morbidity (1,3,5,7). Today, chronic and lifestyle-induced diseases and disabilities dominate morbidity despite the fact that the "old" diseases have not dropped to the low levels found in most Western countries (1,3,5,6,11).…”
Section: Resultsmentioning
confidence: 99%
“…Today, chronic and lifestyle-induced diseases and disabilities dominate morbidity despite the fact that the "old" diseases have not dropped to the low levels found in most Western countries (1,3,5,6,11). In addition, the burden of poor health related to social conditions does not appear to be decreasing (1,21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations